Perencanaan Ruang Publik Berbasis Data Biofisik di Hulu Tukad Badung, Desa Sempidi, Kabupaten Badung - Arcana, I Gede Bagus Windhu; Asmiwyati, I Gusti Agung Ayu Rai; Gunadi, I Gusti Alit (Jurnal Arsitektur Lansekap, 2022)
Public space planning based on biophysic data of upper Tukad Badung, Sempidi Village, Badung District . The Upper Tukad Badung area has the potential for natural sceneries, ecological values and religious socio-culture areas to be developed as a comfortable and safe public zone. The purpose of this research is to identify, analyze the biophysical and social aspects and allocate space for public activities in accordance with the conditions of the Upper Tukad Badung area. The research method used was a survey method using data collection techniques through observation, site documentation, interviews, questionnaires, and literature study. The landscape planning stages included inventory, analysis, synthesis, and landscape planning. The results of spatial synthesis of topographic and vegetation data with descriptive analysis of other data resulted active and passive public zones. The zones were connected with primary and secondary circulation types in a linear pattern. The vegetation plan had three functions;aesthetic conservation, cultivation, and vegetation.